Real-time optimal power flow solution for wind farm integrated power system using evolutionary programming algorithm - Ida Evangeline, S.; Rathika, P. (International journal of environmental science and technology (Tehran), 2021)
In order to satisfy the increasing demand for electricity, a huge burden is levied on the conventional coal-fired thermal power generation units, which affects the environment and human health adversely. To tackle this problem, the clean renewable sources of energy have gained more attention. With time, wind power is expected to contribute more significantly and should be used as much as possible. This has provided much focus to the wind farm integrated power system. But, the unsteady behavior of wind energy has made the operation of wind farm integrated power system more complex. Scenario generation methods are used for tackling the unsteady behavior of wind energy. A persistence method of scenario generation is proposed for solving real-time optimal power flow problem in wind farm integrated power system. The proposed persistence method performs better compared to other recent methods in the literature.